PHYSIOLOGICAL AND SANITARY QUALITY OF SEEDS UNDER TO EARLY SOYBEAN SOWING - ALBRECHT, Leandro Paiola; BRACCINI, Alessandro de Lucca e; SCAPIM, Carlos Alberto; AGUIAR, Celso Gonçalves de; ÁVILA, Marizangela Rizzatti; STÜLP, Marcibela STÜLP (Scientia Agraria, 2008)
An early soybean sowing, especially early maturing varieties is a practice that has been adopted by many growers in the state of Paraná in order to anticipate the harvest of the crop and enhance the fall corn. For this reason, experiments of corn cultivar competition trials were carried out at COODETEC in the county of Palotina, Paraná State, to evaluate the influence of the early sowing on the quality of soybean seeds produced. A randomized block design, during two harvests (2003/2004 and 2004/2005); three early maturing varieties (CD 202, CD 215 and CD 216); and five sowing dates (09/15, 09/30, 10/15, 10/30 and 11/15) were utilized. The physiological trait of soybean seeds was evaluated by the germination test (first and final count); and tetrazolium (vigor and viability) tests. The blotter test was used to evaluate sanitary quality of the seeds. The data were submitted to variance analysis between groups along with all necessary adjustments. The results showed that the sowing dates 30/10, was favorable for the production of seeds with better quality.